2020
DOI: 10.22541/au.159373244.41215753
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between Male Gender, Body Size and Dimension of the Epiglottis

Abstract: Objective: This prospective observational study aims to measure the epiglottic thickness by ultrasonography (US) in healthy volunteers. Methods: Healthy adult volunteers were recruited from the National Taiwan University Hospital between October and November 2019. Exclusion criteria included preexisting airway diseases, neck tumors, and a history of neck operation. Epiglottic thickness was measured at the midpoint, right and left edges of the epiglottis. Age, sex, height, weight, and body mass index (BMI) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…They have concluded that the objective measurements converted to a ratio (such as EW/C3W) could be useful for patients of all ages without difference [18]. Besides, there has been a study on the association of sex, body weight, race, and epiglottic size, despite using sonographic measurement in healthy individuals [19]. This led to a conclusion that male gender and higher body mass index (BMI) are associated with a larger epiglottis.…”
Section: Discussionmentioning
confidence: 99%
“…They have concluded that the objective measurements converted to a ratio (such as EW/C3W) could be useful for patients of all ages without difference [18]. Besides, there has been a study on the association of sex, body weight, race, and epiglottic size, despite using sonographic measurement in healthy individuals [19]. This led to a conclusion that male gender and higher body mass index (BMI) are associated with a larger epiglottis.…”
Section: Discussionmentioning
confidence: 99%